Prophetic Literature in The Poetry Anthology "Makrifat Daun, Daun Makrifat" by Kuntowijoyo - Azizah, Ririn Nurul; Rofiqoh, Rofiqoh (English Education and Literature Journal (E-Jou), 2025)
This research aims to describe and explain the prophetic literature contained in the poetry anthology "Makrifat Daun, Daun Makrifat" by Kuntowijoyo starting from the dimensions of humanization, liberation and transcendence. The method used in this research is descriptive with research results in the form of qualitative data. The primary data source in this research is the poetry anthology "Makrifat Daun, Daun Makrifat" by Kuntowijoyo. Meanwhile, the secondary data source for this research is scientific theories in relevant reading. Thus, this research focuses on words or sentences in poetic stanzas that contain prophetic literature. Data collection steps use listening, note-taking and data classification techniques. Based on the results of the research carried out, several things can be concluded as follows. First, the humanization dimension of prophetic literature includes (1) sincerity and sincerity in carrying out commendable actions, (2) being a person who can benefit others and the environment, showing selfless behavior, (3) the desire to change the world through respect and shaping beautiful history. Second, the prophetic literature dimension of liberation includes (1) freeing oneself or avoiding spiritual alienation, (2) maintaining the quality of hablumminallah, (3) respecting freedom in determining the direction and purpose of life, (4) awareness of the transience of life so that one must continue to struggle and try to build wonderful future. Third, the transcendence dimension of prophetic literature includes (1) a person's longing and seriousness for taqorrub and seeking divine truth so as to obtain truth, guidance and closeness to the divine, (2) as well as reflection on the journey of life that will return to its origin